Assessing the Nigeria Police Force Strategies in Addressing the Rising Crime Rate in Delta and Edo States - Sunday Ori Emese; Akpomuvire Mukoro (Pinisi Journal of Social Science, 2025)
Abstract. This study assesses the strategies employed by the Nigeria Police Force (NPF) to address the rising crime rate in Delta and Edo States, focusing on the effectiveness of community policing, technological innovations, and inter-agency collaboration. The rising crime rate in these states, characterized by kidnappings, armed robbery, cultism, and communal clashes, has created significant security challenges that demand effective law enforcement responses. The objective of this study was to explore the relationship between community policing and crime reduction, assess the role of technological innovations in improving police performance, and examine the impact of inter-agency collaboration on crime control. The study used a quantitative approach, collecting data through a structured questionnaire distributed to security stakeholders, including police officers, community leaders, and residents in Delta and Edo States. The study was anchored on the Routine Activity Theory, which emphasizes how routine daily activities and societal changes influence crime opportunities. Correlation analysis was employed to test the hypotheses with the aid of Statistical Package for Social Science (SPSS) version 23. The findings revealed a strong positive correlation between community policing and crime reduction, as well as between technological innovations and improved police performance. Additionally, inter-agency collaboration was found to be crucial in enhancing the overall effectiveness of crime reduction strategies. The conclusion drawn from this study emphasizes the importance of integrating community-based policing, modern technologies, and inter-agency cooperation in addressing crime in in Delta and Edo States. The study recommended among others that the Nigeria Police Force should invest more in technological tools and foster stronger collaborations between security agencies to effectively combat rising crime rates in Delta and Edo States.